2017
DOI: 10.22603/ssrr.1.2017-0023
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNA transcriptome analysis on hypertrophy of ligamentum flavum in patients with lumbar spinal stenosis

Abstract: Abstract:Introduction: Molecular pathways involved in ligamentum flavum (LF) hypertrophy are still unclarified. The purpose of this study was to characterize LF hypertrophy by microRNA (miRNA) profiling according to the classification of lumbar spinal stenosis (LSS).Methods: Classification of patients with LSS into ligamentous and non-ligamentous cases was conducted by clinical observation and the morphometric parameter adopting the LF/spinal canal area ratio (LSAR) from measurements of magnetic resonance imag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(21 citation statements)
references
References 45 publications
1
20
0
Order By: Relevance
“…Based on transcriptome sequencing, deregulated miRNAs profiling in HLF patients was conducted by Mori et al in which they utilized the Agilent microarray and identified 10 DEMs in hypertrophied LF tissues (n = 10) vs. normal tissues (n = 10) (Mori et al, 2017). In this expression signature, nine miRNAs (miR-1228-3p, miR-1237, miR-30c-2-3p, miR-423-5p, miR-4306, miR-483-5p, miR-514b-5p, miR-516b-5p, and miR-765) were downregulated, and only one (miR-497-5p) was upregulated in the hypertrophied ligaments.…”
Section: Expression Profiling Of Micrornas In Hypertrophy Of Ligamentum Flavummentioning
confidence: 99%
“…Based on transcriptome sequencing, deregulated miRNAs profiling in HLF patients was conducted by Mori et al in which they utilized the Agilent microarray and identified 10 DEMs in hypertrophied LF tissues (n = 10) vs. normal tissues (n = 10) (Mori et al, 2017). In this expression signature, nine miRNAs (miR-1228-3p, miR-1237, miR-30c-2-3p, miR-423-5p, miR-4306, miR-483-5p, miR-514b-5p, miR-516b-5p, and miR-765) were downregulated, and only one (miR-497-5p) was upregulated in the hypertrophied ligaments.…”
Section: Expression Profiling Of Micrornas In Hypertrophy Of Ligamentum Flavummentioning
confidence: 99%
“…109 Moreover, microRNA transcriptome analysis showed that Aryl hydrocarbon receptor and Wnt/β-catenin signaling may also be involved in TGF-β1-induced LF fibrosis ( Figure 2). 110 Together, TGF-β1 not only activates the formation of ECM in fibroblast cells, it also increases the differentiation of fibroblast to myofibroblast by promoting or triggering the processes of producing ECM.…”
Section: Tgf-βmentioning
confidence: 99%
“…Our data also showed that TGF-β1 could effectively promote the expression of Col-I, α-SMA, and Col-III and result in LF cell fibrosis in a dose-dependent manner. According to previous literatures [ 11 , [43] , [44] , [45] ], 10 miRNAs relative to fibrosis were selected as candidates; the RT-qPCR validation of these candidates partially matched the results reported in a previous study [ 46 ]. Since the amelioration of LFH after the EV injection was found, we hypothesised that the miRNAs enriched in the EVs would take responsibility for this amelioration.…”
Section: Discussionmentioning
confidence: 85%